High-strength light-weight aluminum alloy and preparation method thereof

By adding modified graphene oxide and titanium-containing organic polymer to the aluminum alloy, the problems of lightweight and poor strength of aluminum alloy are solved, and higher lightweight and strength are achieved, and corrosion resistance is improved.

CN119410970AInactive Publication Date: 2025-02-11GUANGDONG ZHUOHANG METAL TECHNOLOGY CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411536547.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, aluminum alloys have poor lightweighting and strength, making it difficult to meet the demand for high-strength lightweight materials in the fields of sports equipment and other fields.

Method used

Modified graphene oxide was prepared by combining graphite powder, potassium permanganate, cetyl ammonium bromide, 2-amino terephthalic acid and tetrabutyl titanate. and titanium-containing organic polymers, added to the aluminum alloy to improve its lightweight and strength.

Benefits of technology

It significantly improves the lightweight and strength of aluminum alloys, extends its service life, and enhances corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111685870000041
    Figure BDA0005111685870000041
  • Figure BDA0005111685870000051
    Figure BDA0005111685870000051
  • Figure BDA0005111685870000171
    Figure BDA0005111685870000171
Patent Text Reader

Abstract

The invention discloses a high-strength light-weight aluminum alloy and a preparation method thereof, and belongs to the technical field of aluminum alloy preparation. The high-strength light-weight aluminum alloy is composed of, by weight, 80-90 parts of composite alloy, 11-15 parts of composite organic refiner and 23-28 parts of organic coating, the composite organic refiner is prepared from graphite powder, potassium permanganate, hexadecyl ammonium bromide, 2-aminoterephthalic acid and tetrabutyl titanate, and the organic coating is prepared from 4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'-dihydroxy-4, 4 '-dihydroxy-4, 4'- The aluminum alloy is prepared from 4, 4 '-(acetylene-1, 2-diyl) diphthalic anhydride, 4, 4'-(4, 4 '-diaminodiphenyl ether, 4, 4'-(acetylene-1, 2-diyl) diphthalic anhydride, 4, 4 '-oxybisphphthalic anhydride, 3, 4'-diaminodiphenyl ether and 3-aminophenylacetylene, and the aluminum alloy prepared through the method has excellent strength and light weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy preparation, and in particular relates to a high-strength lightweight aluminum alloy and a preparation method thereof. Background Art

[0002] With the continuous development of modern sports competition, the performance requirements for sports equipment are increasing day by day. Lightweight, high strength, wear resistance, corrosion resistance and good processing performance have become important criteria for the selection of sports equipment materials. Therefore, high-strength and lightweight aluminum alloys have been widely used and studied in the field of sports equipment due to their unique advantages. In the field of sports equipment, lightweight is one of the key factors to improve sports performance. For athletes, the weight of the equipment is directly related to their sports efficiency, endurance and competitive state. Lightweight equipment can reduce the burden on athletes, improve their sports flexibility and reaction speed, and thus gain an advantage in the competition.

[0003] The Chinese invention patent application with publication number CN 114369745 B discloses a high-strength aluminum alloy and a preparation method and application thereof. The high-strength aluminum alloy of the invention includes the following components in mass percentage: Cu: 0.32-0.53%, Fe: 0.12-0.25%, Mn: 0.55-0.9%, Si: 0.9-1.36%, Mg: 0.53-0.85%, Cr: 0.15-0.22%, Y: 0.1-0.15%, Ti: 0.01-0.04%, the total amount of impurities is ≤0.15%, and the balance is Al. The high-strength aluminum alloy prepared by the invention scheme has good mechanical properties and crushing properties, and can well meet the user's demand for lightweight materials. However, the lightweight and strength of the aluminum alloy material prepared by this method still have room for improvement. Summary of the invention

[0004] The object of the present invention is to provide a high-strength and lightweight aluminum alloy and a preparation method thereof, so as to solve the technical problems of lightweight and poor strength of aluminum alloy in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention provides a high-strength lightweight aluminum alloy, which is composed of the following components in parts by weight: 80-90 parts of a composite alloy, 11-15 parts of a composite organic refiner, and 23-28 parts of an organic coating, wherein the composite organic refiner is prepared from graphite powder, potassium permanganate, hexadecyl ammonium bromide, 2-aminoterephthalic acid and tetrabutyl titanate, and the organic coating is prepared from 4,4'-diaminodiphenyl ether, 4,4'-(acetylene-1,2-diyl) diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,4'-diaminodiphenyl ether and 3-aminophenylacetylene.

[0007] Preferably, the composite alloy consists of the following elements in percentage by mass: Mg: 0.5-0.87%, Zn: 0.5-0.84%, Cu: 0.41-0.55%, Mn: 0.4-0.76%, Si: 0.91-1.12%, La: 0.12-0.15%, Ce: 0.02-0.06%, Zr: 0.05-0.09%, and the balance is Al.

[0008] Preferably, the preparation method of the composite organic refiner comprises the following steps:

[0009] Q1: Add graphite powder to sulfuric acid, add potassium permanganate in an ice water bath, stir, and keep warm to react. After the reaction is completed, a graphene oxide solution is obtained. At the same time, hexadecyl ammonium bromide is added to deionized water, stirred evenly, and then added dropwise to the graphene oxide solution. After the addition is completed, deionized water is added, and hydrogen peroxide is added during the stirring process. After the addition is completed, centrifugal washing is performed, and freeze-drying is performed to obtain modified graphene oxide;

[0010] Q2: Add 2-aminoterephthalic acid to a container containing a mixed solution of N,N-dimethylformamide and anhydrous methanol, then add tetrabutyl titanate, stir at room temperature to obtain a mixed solution, immerse the modified graphene oxide in the mixed solution, heat to react, cool and filter, wash, vacuum dry, and crush to obtain a composite organic refiner.

[0011] In the above process, graphite powder is first oxidized into graphene oxide containing carboxyl and hydroxyl functional groups, and then the long-chain alkyl of hexadecyl ammonium bromide as a cationic surfactant can interact with the negative charge on the surface of the graphene oxide and adsorb on the surface of the graphene oxide, and then further oxidized by hydrogen peroxide to obtain modified graphene oxide; at the same time, tetrabutyl titanate is hydrolyzed and condensed to form a titanium oxide network, and 2-aminoterephthalic acid can coordinate or bond with the titanium oxide network through amino groups to form a mixed solution containing titanium-containing organic polymers, and then the modified graphene oxide is mixed with the titanium-containing organic polymer to obtain a composite organic refiner.

[0012] Preferably, in Q1, the usage ratio of graphite powder, sulfuric acid, potassium permanganate, hexadecyl ammonium bromide and hydrogen peroxide is (2-4) g: (100-200) mL: (10-18) g: (1-1.5) g: (0.5-1.5) mL, the particle size of graphite powder is 8000 mesh, the volume fraction of sulfuric acid is 98vt%, the stirring time is 30-45 min, the insulation reaction temperature is 30-35°C, the time is 2-4 h, and the dropwise addition time is 45-60 min.

[0013] Preferably, in Q2, the dosage ratio of 2-aminoterephthalic acid, N,N-dimethylformamide, anhydrous methanol, tetrabutyl titanate and modified graphene oxide is (1.95-3.9) g: (70-150) mL: (3.6-7.5) mL: (0.93-1.8) g: (8-12) g, the stirring time at room temperature is 10-15 min, the heating reaction temperature is 120-140°C, the reaction time is 20-24 h, and the product is washed with anhydrous methanol and distilled water. The vacuum drying temperature is 50-60°C and the time is 10-12 h.

[0014] Preferably, the method for preparing the organic coating comprises the following steps:

[0015] S1: Add 4,4'-diaminodiphenyl ether to a container containing N,N-dimethylformamide, stir at low temperature under nitrogen protection, then add 4,4'-(acetylene-1,2-diyl) diphthalic anhydride and 4,4'-oxydiphthalic anhydride to the container, stir to react, then place it in a polytetrafluoroethylene container, react at low temperature, and after the reaction is completed, heat and solidify to obtain component 1;

[0016] S2: 4,4'-diaminodiphenyl ether and 3,4'-diaminodiphenyl ether are added to a container, followed by N,N-dimethylformamide, and the container is placed in an ice-water bath environment, nitrogen is introduced and mechanical stirring is performed, and then 4,4'-oxydiphthalic anhydride and N,N-dimethylformamide are added to the container for reaction. After the reaction is completed, 3-aminophenylacetylene is added to continue the reaction. After the reaction is completed, the container is placed in a polytetrafluoroethylene container for low-temperature reaction. After the reaction is completed, the mixture, N,N-dimethylformamide and xylene are mixed and placed in a reaction device equipped with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, and the mixture is stirred rapidly and maintained in an azeotropic state to remove water. After heating and refluxing, the reaction is stopped, cooled to room temperature, the reaction solution is poured into ethanol, stirred, filtered, washed, and vacuum dried to obtain component 2;

[0017] S3: Component 1 and component 2 are mixed, and magnetically stirred at room temperature. After the stirring is completed, degassing is performed to obtain an organic coating.

[0018] In the above process, the synthetic reaction formula of component 1 is as follows:

[0019]

[0020] The synthetic reaction formula of component 2 is as follows:

[0021]

[0022] Preferably, in S1, the amount ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylformamide, 4,4'-(acetylene-1,2-diyl) diphthalic anhydride and 4,4'-oxydiphthalic anhydride is (4-8) g: (41-80) mL: (3-6) g: (3.1-6.3) g, the low-temperature stirring temperature is 0-2°C, the stirring time is 30-45 min, the stirring reaction time is 8-12 h, the low-temperature reaction temperature is -15 to -20°C, the time is 10-12 h, and the heating curing process is: first, heat treatment at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, then heat treatment at 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate is maintained at 5°C / min.

[0023] Preferably, in S2, the amount ratio of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-oxydiphthalic anhydride and 3-aminophenylacetylene is (3.75-7.5) g: (1.25-2.5) g: (15.15-30.3) g: (5.86-11.72) g, the mechanical stirring time is 30-45 min, the reaction time is 5-7 h, the continued reaction time is 2-3 h, the low temperature reaction temperature is -15 to -20 ° C, the reaction time is 10-12 h, the mixture, N,N -The dosage ratio of dimethylformamide and xylene is (45-50) mL: (45-55) mL: (25-33) mL, the dehydration time is 8-10 h, and it is washed with ethanol 3-5 times. The vacuum drying temperature is 140-160°C and the time is 2-3 h; in S3, the dosage ratio of component 1 and component 2 is (20-23) g: (10-12) g, the magnetic stirring time is 30-45 min, and a vacuum degassing instrument is used for degassing treatment, the vacuum degree is 1 kPa, the rotation speed is 2000 rpm, and the running time is 3 min.

[0024] Preferably, the method for preparing the high-strength lightweight aluminum alloy comprises the following steps:

[0025] Step (1): adding the composite alloy material into a smelting furnace and heating it until it is melted, introducing nitrogen during the smelting process, then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting;

[0026] Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention first prepares a composite organic refiner with graphite powder, potassium permanganate, hexadecyl ammonium bromide, 2-aminoterephthalic acid and tetrabutyl titanate, and then prepares an organic coating with 4,4'-diaminodiphenyl ether, 4,4'-(acetylene-1,2-diyl) diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,4'-diaminodiphenyl ether and 3-aminophenylacetylene. Adding the composite organic refiner and applying the organic coating in the process of preparing aluminum alloy can effectively improve the weight and strength of the aluminum alloy and broaden the use range and service life of the aluminum alloy.

[0029] 2. The present invention uses graphite powder, potassium permanganate, hexadecyl ammonium bromide, 2-aminoterephthalic acid and tetrabutyl titanate to prepare a composite organic refiner. The composite organic refiner is added to the preparation process of aluminum alloy to effectively improve its lightweight degree. The modified graphene oxide and titanium-containing organic polymer contained in the composite organic refiner can serve as the core of heterogeneous nucleation in the aluminum alloy melt, increase the nucleation points, and refine the grains. The modified graphene oxide has a large specific surface area and rich functional groups, and can adsorb and stabilize heterogeneous atoms or ions in the aluminum alloy melt. To promote the nucleation process, titanium-containing organic polymers can decompose in the aluminum alloy melt to produce titanium atoms or titanium oxides, which act as effective nucleating agents to further refine the grains. Refining the grains can increase the grain boundaries that are effective barriers to crack propagation. After grain refinement, cracks need to constantly change direction when propagating in the material, consuming more energy, thereby improving the strength and toughness of the aluminum alloy. In addition, due to the increase in the number of grain boundaries and the optimization of the internal structure of the grains, the material can withstand a greater load under the same volume, thereby reducing the dosage and achieving lightweight while meeting the strength requirements.

[0030] 3. The present invention uses 4,4'-diaminodiphenyl ether, 4,4'-(acetylene-1,2-diyl) diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,4'-diaminodiphenyl ether and 3-aminophenylacetylene to prepare an organic coating, and the obtained organic coating is uniformly applied to the surface of an aluminum alloy casting, which can effectively improve the strength and corrosion resistance of the aluminum alloy. The polyimide structure contained in the organic coating has excellent mechanical properties and thermal stability. When it is applied to the surface of the aluminum alloy and cured, the organic coating can form a dense polymer network, thereby giving the coating high strength and rigidity, and the amide bonds contained in the organic coating have high strength, can resist damage from external forces, and maintain its integrity; at the same time, the aromatic rings and amide bonds contained in the organic coating can form a stable chemical structure, which is not easily destroyed by corrosive media, and effectively improves its corrosion resistance. DETAILED DESCRIPTION

[0031] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: This example discloses a method for preparing a composite organic refiner, comprising the following steps:

[0033] Q1: Add 3g of graphite powder with a particle size of 8000 mesh to 150mL of sulfuric acid with a volume fraction of 98vt%, add 14g of potassium permanganate in an ice-water bath environment, stir for 45min, and keep warm at 35℃ for 4h to obtain a graphene oxide solution after the reaction. At the same time, add 1.25g of hexadecyl ammonium bromide to 100mL of deionized water, stir evenly and then drop it into the graphene oxide solution. The dropping time is 60min. After the dropping is completed, add 20mL of deionized water, add 1mL of hydrogen peroxide during the stirring process, and after the dropping is completed, centrifuge and wash, and freeze-dry to obtain modified graphene oxide;

[0034] Q2: 3.05 g of 2-aminoterephthalic acid was added to a container containing a mixed solution of 105 mL of N,N-dimethylformamide and 5.2 mL of anhydrous methanol, followed by adding 1.35 g of tetrabutyl titanate. The mixture was stirred at room temperature for 15 min to obtain a mixed solution. 10 g of modified graphene oxide was immersed in the mixed solution, heated at 140 ° C for reaction for 24 h, cooled and filtered, washed with anhydrous methanol and distilled water, vacuum dried at 60 ° C for 12 h, and crushed to obtain a composite organic refiner.

[0035] This embodiment discloses a method for preparing an organic coating, comprising the following steps:

[0036] S1: 6 g of 4,4'-diaminodiphenyl ether was added to a container containing 60 mL of N,N-dimethylformamide, and stirred at 0°C for 45 min under nitrogen protection. Then, 4.5 g of 4,4'-(acetylene-1,2-diyl)phthalic anhydride and 4.7 g of 4,4'-oxydiphthalic anhydride were added to the container, and stirred for reaction for 12 h. Then, it was placed in a polytetrafluoroethylene container and reacted at -20°C for 12 h. After the reaction was completed, it was heated and cured. The process was: first, heat-treated at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, and then heated to 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate was maintained at 5°C / min to obtain component 1;

[0037] S2: 5.5 g of 4,4'-diaminodiphenyl ether and 1.87 g of 3,4'-diaminodiphenyl ether were added to the container, followed by 30 mL of N,N-dimethylformamide. The container was placed in an ice-water bath, nitrogen was introduced, and mechanical stirring was performed for 30 min. Then, 27.8 g of 4,4'-oxydiphthalic anhydride and 30 mL of N,N-dimethylformamide were added to the container, and the reaction was continued for 7 h. After the reaction was completed, 8.52 g of 3-aminophenylacetylene, continue to react for 3 hours, after the reaction is completed, place it in a polytetrafluoroethylene container, react at -20°C for 12 hours, after the reaction is completed, mix 47.5 mL of the mixture, 50 mL of N,N-dimethylformamide and 29 mL of xylene, place it in a reaction device with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, stir rapidly and maintain azeotropic state to remove water for 10 hours, after heating and reflux, stop the reaction, cool to room temperature, pour the reaction solution into ethanol, stir, filter, wash with ethanol 5 times, and vacuum dry at 160°C for 3 hours to obtain component 2;

[0038] S3: 21.5 g of component 1 and 11 g of component 2 were mixed, and magnetically stirred at room temperature for 45 min. After the stirring, a vacuum deaerator was used for deaeration at a vacuum degree of 1 kPa, a rotation speed of 2000 rpm, and a running time of 3 min to obtain an organic coating.

[0039] This embodiment discloses a high-strength and lightweight aluminum alloy, which is composed of the following components in parts by weight: 83 parts of a composite alloy, 13 parts of a composite organic refiner, and 25.5 parts of an organic coating.

[0040] This embodiment discloses a method for preparing a high-strength and lightweight aluminum alloy, comprising the following steps:

[0041] Step (1): adding a composite alloy material having the following mass percentage elements (Mg: 0.63%, Zn: 0.67%, Cu: 0.48%, Mn: 0.53%, Si: 1.05%, La: 0.14%, Ce: 0.04%, Zr: 0.08%, and the balance Al) into a smelting furnace and heating to melt, introducing nitrogen during the smelting process, and then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting;

[0042] Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

[0043] Example 2: This example discloses a method for preparing a composite organic refiner, comprising the following steps:

[0044] Q1: Add 2g of graphite powder with a particle size of 8000 mesh to 200mL of sulfuric acid with a volume fraction of 98vt%, add 18g of potassium permanganate in an ice-water bath environment, stir for 45min, and keep warm at 35℃ for 4h to obtain a graphene oxide solution after the reaction. At the same time, add 1g of hexadecyl ammonium bromide to 100mL of deionized water, stir evenly and then drop it into the graphene oxide solution. The dropping time is 60min. After the dropping is completed, add 20mL of deionized water, add 1.5mL of hydrogen peroxide during the stirring process, and after the dropping is completed, centrifuge and wash, and freeze-dry to obtain modified graphene oxide;

[0045] Q2: 1.95 g of 2-aminoterephthalic acid was added to a container containing a mixed solution of 70 mL of N,N-dimethylformamide and 3.6 mL of anhydrous methanol, followed by adding 0.93 g of tetrabutyl titanate. The mixture was stirred at room temperature for 15 min to obtain a mixed solution. 8 g of modified graphene oxide was immersed in the mixed solution, heated at 140°C for reaction for 24 h, cooled and filtered, washed with anhydrous methanol and distilled water, vacuum dried at 60°C for 12 h, and crushed to obtain a composite organic refiner.

[0046] This embodiment discloses a method for preparing an organic coating, comprising the following steps:

[0047] S1: 4 g of 4,4'-diaminodiphenyl ether was added to a container containing 41 mL of N,N-dimethylformamide, and stirred at 0°C for 45 min under nitrogen protection. Then, 3 g of 4,4'-(acetylene-1,2-diyl)phthalic anhydride and 3.1 g of 4,4'-oxydiphthalic anhydride were added to the container, and the mixture was stirred for reaction for 12 h. The mixture was then placed in a polytetrafluoroethylene container and reacted at -20°C for 12 h. After the reaction was completed, the mixture was heated and cured. The process was as follows: first, the mixture was heat-treated at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, and then the mixture was heated to 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate was maintained at 5°C / min to obtain component 1.

[0048] S2: 3.75 g of 4,4'-diaminodiphenyl ether and 1.25 g of 3,4'-diaminodiphenyl ether were added to the container, followed by 30 mL of N,N-dimethylformamide. The container was placed in an ice-water bath, nitrogen was introduced, and mechanical stirring was performed for 30 min. Then, 15.15 g of 4,4'-oxydiphthalic anhydride and 30 mL of N,N-dimethylformamide were added to the container, and the reaction was continued for 7 h. After the reaction was completed, 5.86 g of 3-aminophenylacetylene, continue to react for 3 hours, after the reaction is completed, place it in a polytetrafluoroethylene container, react at -20°C for 12 hours, after the reaction is completed, mix 45 mL of the mixture, 45 mL of N,N-dimethylformamide and 25 mL of xylene, place it in a reaction device with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, stir rapidly and maintain azeotropic state to remove water for 10 hours, after heating and reflux, stop the reaction, cool to room temperature, pour the reaction solution into ethanol, stir, filter, wash with ethanol 5 times, and vacuum dry at 160°C for 3 hours to obtain component 2;

[0049] S3: 20 g of component 1 and 10 g of component 2 were mixed, and magnetically stirred at room temperature for 45 min. After the stirring, a vacuum deaerator was used for deaeration at a vacuum degree of 1 kPa, a rotation speed of 2000 rpm, and a running time of 3 min to obtain an organic coating.

[0050] This embodiment discloses a high-strength and lightweight aluminum alloy, which is composed of the following components in parts by weight: 80 parts of a composite alloy, 11 parts of a composite organic refiner, and 23 parts of an organic coating.

[0051] This embodiment discloses a method for preparing a high-strength and lightweight aluminum alloy, comprising the following steps:

[0052] Step (1): adding a composite alloy material having the following mass percentage elements (Mg: 0.5%, Zn: 0.5%, Cu: 0.41%, Mn: 0.4%, Si: 0.91%, La: 0.12%, Ce: 0.02%, Zr: 0.05%, and the balance is Al) into a smelting furnace and heating to melt, introducing nitrogen during the smelting process, then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting;

[0053] Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

[0054] Embodiment 3: This embodiment discloses a method for preparing a composite organic refiner, comprising the following steps:

[0055] Q1: Add 4g of graphite powder with a particle size of 8000 mesh to 100mL of sulfuric acid with a volume fraction of 98vt%, add 10g of potassium permanganate in an ice-water bath environment, stir for 45min, and keep warm at 35℃ for 4h to obtain a graphene oxide solution after the reaction. At the same time, add 1.5g of hexadecyl ammonium bromide to 100mL of deionized water, stir evenly and then drop it into the graphene oxide solution. The dropping time is 60min. After the dropping is completed, add 20mL of deionized water, add 0.5mL of hydrogen peroxide during the stirring process, and after the dropping is completed, centrifuge and wash, and freeze-dry to obtain modified graphene oxide;

[0056] Q2: 3.9 g of 2-aminoterephthalic acid was added to a container containing a mixed solution of 150 mL of N,N-dimethylformamide and 7.5 mL of anhydrous methanol, followed by adding 1.8 g of tetrabutyl titanate. The mixture was stirred at room temperature for 15 min to obtain a mixed solution. 12 g of modified graphene oxide was immersed in the mixed solution, heated at 140 ° C for reaction for 24 h, cooled and filtered, washed with anhydrous methanol and distilled water, vacuum dried at 60 ° C for 12 h, and crushed to obtain a composite organic refiner.

[0057] This embodiment discloses a method for preparing an organic coating, comprising the following steps:

[0058] S1: 8 g of 4,4'-diaminodiphenyl ether was added to a container containing 80 mL of N,N-dimethylformamide, and stirred at 0°C for 45 min under nitrogen protection. Then, 6 g of 4,4'-(acetylene-1,2-diyl)phthalic anhydride and 6.3 g of 4,4'-oxydiphthalic anhydride were added to the container, and the mixture was stirred for reaction for 12 h. The mixture was then placed in a polytetrafluoroethylene container and reacted at -20°C for 12 h. After the reaction was completed, the mixture was heated and cured. The process was as follows: first, the mixture was heat-treated at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, and then the mixture was heated to 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate was maintained at 5°C / min to obtain component 1.

[0059] S2: 7.5 g of 4,4'-diaminodiphenyl ether and 2.5 g of 3,4'-diaminodiphenyl ether were added to the container, followed by 30 mL of N,N-dimethylformamide. The container was placed in an ice-water bath, nitrogen was introduced and mechanically stirred for 30 min, and then 30.3 g of 4,4'-oxydiphthalic anhydride and 30 mL of N,N-dimethylformamide were added to the container. The reaction was continued for 7 h. After the reaction was completed, 11.72 g of 3-aminophenylacetylene, continue to react for 3 hours, after the reaction is completed, place it in a polytetrafluoroethylene container, react at -20°C for 12 hours, after the reaction is completed, mix 50 mL of the mixture, 55 mL of N,N-dimethylformamide and 33 mL of xylene, place it in a reaction device with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, stir rapidly and maintain azeotropic state to remove water for 10 hours, after heating and reflux, stop the reaction, cool to room temperature, pour the reaction solution into ethanol, stir, filter, wash with ethanol 5 times, and vacuum dry at 160°C for 3 hours to obtain component 2;

[0060] S3: 23 g of component 1 and 12 g of component 2 were mixed, and magnetically stirred at room temperature for 45 min. After stirring, a vacuum deaerator was used for deaeration at a vacuum degree of 1 kPa, a rotation speed of 2000 rpm, and a running time of 3 min to obtain an organic coating.

[0061] This embodiment discloses a high-strength and lightweight aluminum alloy, which is composed of the following components in parts by weight: 90 parts of a composite alloy, 15 parts of a composite organic refiner, and 28 parts of an organic coating.

[0062] This embodiment discloses a method for preparing a high-strength and lightweight aluminum alloy, comprising the following steps:

[0063] Step (1): adding a composite alloy material having the following mass percentage elements (Mg: 0.87%, Zn: 0.84%, Cu: 0.55%, Mn: 0.76%, Si: 1.12%, La: 0.15%, Ce: 0.06%, Zr: 0.09%, and the balance Al) into a smelting furnace and heating to melt, introducing nitrogen during the smelting process, then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting;

[0064] Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

[0065] Embodiment 4: This embodiment discloses a method for preparing a composite organic refiner, comprising the following steps:

[0066] Q1: Add 2.5g of graphite powder with a particle size of 8000 mesh to 120mL of sulfuric acid with a volume fraction of 98vt%, add 12g of potassium permanganate in an ice-water bath environment, stir for 45min, and keep warm at 35℃ for 4h to obtain a graphene oxide solution after the reaction. At the same time, add 1.1g of hexadecyl ammonium bromide to 100mL of deionized water, stir evenly and then drop it into the graphene oxide solution. The dropping time is 60min. After the dropwise addition is completed, add 20mL of deionized water, add 0.75mL of hydrogen peroxide during the stirring process, and after the dropwise addition is completed, centrifuge and wash, and freeze-dry to obtain modified graphene oxide;

[0067] Q2: Add 2.18 g of 2-aminoterephthalic acid into a container containing a mixed solution of 120 mL of N,N-dimethylformamide and 4.1 mL of anhydrous methanol, then add 1.15 g of tetrabutyl titanate, stir at room temperature for 15 min to obtain a mixed solution, soak 9 g of modified graphene oxide in the mixed solution, heat to react at 140°C for 24 h, cool and filter, wash with anhydrous methanol and distilled water, vacuum dry at 60°C for 12 h, and crush to obtain a composite organic refiner.

[0068] This embodiment discloses a method for preparing an organic coating, comprising the following steps:

[0069] S1: 5 g of 4,4'-diaminodiphenyl ether was added to a container containing 50 mL of N,N-dimethylformamide, and stirred at 0°C for 45 min under nitrogen protection. Then, 4 g of 4,4'-(acetylene-1,2-diyl)phthalic anhydride and 3.8 g of 4,4'-oxydiphthalic anhydride were added to the container, and the mixture was stirred for reaction for 12 h. The mixture was then placed in a polytetrafluoroethylene container and reacted at -20°C for 12 h. After the reaction was completed, the mixture was heated and cured. The process was as follows: first, the mixture was heat-treated at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, and then the mixture was heated to 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate was maintained at 5°C / min to obtain component 1.

[0070] S2: 4.27 g of 4,4'-diaminodiphenyl ether and 1.63 g of 3,4'-diaminodiphenyl ether were added to the container, followed by 30 mL of N,N-dimethylformamide. The container was placed in an ice-water bath, nitrogen was introduced, and mechanical stirring was performed for 30 min. Then, 21.17 g of 4,4'-oxydiphthalic anhydride and 30 mL of N,N-dimethylformamide were added to the container, and the reaction was continued for 7 h. After the reaction was completed, 7.15 g of 3-aminophenylacetylene, continue to react for 3 hours, after the reaction is completed, place it in a polytetrafluoroethylene container, react at -20°C for 12 hours, after the reaction is completed, mix 46 mL of the mixture, 48 mL of N,N-dimethylformamide and 27 mL of xylene, place it in a reaction device with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, stir rapidly and maintain azeotropic state to remove water for 10 hours, after heating and reflux, stop the reaction, cool to room temperature, pour the reaction solution into ethanol, stir, filter, wash with ethanol 5 times, and vacuum dry at 160°C for 3 hours to obtain component 2;

[0071] S3: 22 g of component 1 and 10.5 g of component 2 were mixed, and magnetically stirred at room temperature for 45 min. After the stirring, a vacuum deaerator was used for deaeration at a vacuum degree of 1 kPa, a rotation speed of 2000 rpm, and a running time of 3 min to obtain an organic coating.

[0072] The present embodiment discloses a high-strength and lightweight aluminum alloy, which is composed of the following components in parts by weight: 82 parts of a composite alloy, 12 parts of a composite organic refiner, and 24 parts of an organic coating.

[0073] This embodiment discloses a method for preparing a high-strength and lightweight aluminum alloy, comprising the following steps:

[0074] Step (1): adding a composite alloy material having the following mass percentage elements (Mg: 0.57%, Zn: 0.62%, Cu: 0.43%, Mn: 0.45%, Si: 0.98%, La: 0.13%, Ce: 0.03%, Zr: 0.07%, and the balance Al) into a smelting furnace and heating to melt, introducing nitrogen during the smelting process, and then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting;

[0075] Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

[0076] Comparative Example 1: Compared with Example 1, in the process of preparing the composite organic refining agent in Comparative Example 1, tetrabutyl titanate is not added, and other conditions remain unchanged.

[0077] Comparative Example 2: Compared with Example 1, in the process of preparing the organic coating in Comparative Example 2, no 4,4'-diaminodiphenyl ether was added, and other conditions remained unchanged.

[0078] Comparative Example 3: Compared with Example 1, in the process of preparing the high-strength and lightweight aluminum alloy in Comparative Example 3, no composite organic refiner is added, and other conditions remain unchanged.

[0079] Comparative Example 4: Compared with Example 1, in the process of preparing the high-strength lightweight aluminum alloy, no organic coating is applied in Comparative Example 4, and other conditions remain unchanged.

[0080] Experimental example: measuring sample at 1cm 3 The mass under volume, the corrosion resistance of the samples was tested according to GB / T 10125-2021, and the strength of the samples was tested according to GB / T 228.1-2010. The test results are shown in Table 1:

[0081] Table 1

[0082]

[0083] From the test results in Table 1, it can be seen that the aluminum alloys prepared in Examples 1-4 of the present invention have light weight, excellent corrosion resistance and strength. From the comparison between Comparative Example 1 and Examples 1-4, it can be seen that the addition of tetrabutyl titanate can effectively improve the lightweight and strength of the aluminum alloy; from the comparison between Comparative Example 2 and Examples 1-4, it can be seen that the addition of 4,4'-diaminodiphenyl ether can effectively improve the corrosion resistance and strength of the aluminum alloy; from the comparison between Comparative Example 3 and Examples 1-4, it can be seen that the addition of a composite organic refiner can effectively improve the lightweight and strength of the aluminum alloy; from the comparison between Comparative Example 4 and Examples 1-4, it can be seen that the coating of an organic coating can effectively improve the corrosion resistance and strength of the aluminum alloy.

[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0085] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-strength and lightweight aluminum alloy, characterized in that: The invention is composed of the following components in parts by weight: 80-90 parts of a composite alloy, 11-15 parts of a composite organic refiner, and 23-28 parts of an organic coating, wherein the composite organic refiner is prepared from graphite powder, potassium permanganate, hexadecyl ammonium bromide, 2-aminoterephthalic acid, and tetrabutyl titanate, and the organic coating is prepared from 4,4'-diaminodiphenyl ether, 4,4'-(acetylene-1,2-diyl)phthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,4'-diaminodiphenyl ether, and 3-aminophenylacetylene.

2. The high-strength and lightweight aluminum alloy according to claim 1, characterized in that: The composite alloy consists of the following elements in percentage by mass: Mg: 0.5-0.87%, Zn: 0.5-0.84%, Cu: 0.41-0.55%, Mn: 0.4-0.76%, Si: 0.91-1.12%, La: 0.12-0.15%, Ce: 0.02-0.06%, Zr: 0.05-0.09%, and the balance is Al.

3. The high-strength and lightweight aluminum alloy according to claim 1, characterized in that: The preparation method of the composite organic refiner comprises the following steps: Q1: Add graphite powder to sulfuric acid, add potassium permanganate in an ice water bath, stir, and keep warm to react. After the reaction is completed, a graphene oxide solution is obtained. At the same time, hexadecyl ammonium bromide is added to deionized water, stirred evenly, and then added dropwise to the graphene oxide solution. After the addition is completed, deionized water is added, and hydrogen peroxide is added during the stirring process. After the addition is completed, centrifugal washing is performed, and freeze-drying is performed to obtain modified graphene oxide; Q2: Add 2-aminoterephthalic acid to a container containing a mixed solution of N,N-dimethylformamide and anhydrous methanol, then add tetrabutyl titanate, stir at room temperature to obtain a mixed solution, immerse the modified graphene oxide in the mixed solution, heat to react, cool and filter, wash, vacuum dry, and crush to obtain a composite organic refiner.

4. The high-strength and lightweight aluminum alloy according to claim 3, characterized in that: In the Q1, the usage ratio of graphite powder, sulfuric acid, potassium permanganate, hexadecyl ammonium bromide and hydrogen peroxide is (2-4) g: (100-200) mL: (10-18) g: (1-1.5) g: (0.5-1.5) mL, the particle size of the graphite powder is 8000 mesh, the volume fraction of sulfuric acid is 98vt%, the stirring time is 30-45 min, the insulation reaction temperature is 30-35° C., the time is 2-4 h, and the dropwise addition time is 45-60 min.

5. The high-strength and lightweight aluminum alloy according to claim 3, characterized in that: In Q2, the dosage ratio of 2-aminoterephthalic acid, N,N-dimethylformamide, anhydrous methanol, tetrabutyl titanate and modified graphene oxide is (1.95-3.9) g: (70-150) mL: (3.6-7.5) mL: (0.93-1.8) g: (8-12) g, the stirring time at room temperature is 10-15 min, the heating reaction temperature is 120-140° C., the reaction time is 20-24 h, and the product is washed with anhydrous methanol and distilled water. The vacuum drying temperature is 50-60° C. and the time is 10-12 h.

6. The high-strength and lightweight aluminum alloy according to claim 1, characterized in that: The method for preparing the organic coating comprises the following steps: S1: Add 4,4'-diaminodiphenyl ether to a container containing N,N-dimethylformamide, stir at low temperature under nitrogen protection, then add 4,4'-(acetylene-1,2-diyl) diphthalic anhydride and 4,4'-oxydiphthalic anhydride to the container, stir to react, then place it in a polytetrafluoroethylene container, react at low temperature, and after the reaction is completed, heat and solidify to obtain component 1; S2: 4,4'-diaminodiphenyl ether and 3,4'-diaminodiphenyl ether are added to a container, followed by N,N-dimethylformamide, and the container is placed in an ice-water bath environment, nitrogen is introduced and mechanical stirring is performed, and then 4,4'-oxydiphthalic anhydride and N,N-dimethylformamide are added to the container for reaction. After the reaction is completed, 3-aminophenylacetylene is added to continue the reaction. After the reaction is completed, the container is placed in a polytetrafluoroethylene container for low-temperature reaction. After the reaction is completed, the mixture, N,N-dimethylformamide and xylene are mixed and placed in a reaction device equipped with a mechanical stirrer, a reflux condenser, a thermometer and a water separator, and the mixture is stirred rapidly and maintained in an azeotropic state to remove water. After heating and refluxing, the reaction is stopped, cooled to room temperature, the reaction solution is poured into ethanol, stirred, filtered, washed, and vacuum dried to obtain component 2; S3: Component 1 and component 2 are mixed, and magnetically stirred at room temperature. After the stirring is completed, degassing is performed to obtain an organic coating.

7. The high-strength and lightweight aluminum alloy according to claim 6, characterized in that: In the S1, the amount ratio of 4,4'-diaminodiphenyl ether, N,N-dimethylformamide, 4,4'-(acetylene-1,2-diyl) diphthalic anhydride and 4,4'-oxydiphthalic anhydride is (4-8) g: (41-80) mL: (3-6) g: (3.1-6.3) g, the low-temperature stirring temperature is 0-2°C, the stirring time is 30-45 min, the stirring reaction time is 8-12 h, the low-temperature reaction temperature is -15 to -20°C, and the reaction time is 10-12 h. The heating curing process is: first, heat treatment at 50°C, 75°C, 100°C, 125°C, 150°C, 175°C, and 200°C for 1 h each, then heat treatment at 230°C, 260°C, 290°C, and 320°C for 1 h each, and the heating rate is maintained at 5°C / min.

8. The high-strength and lightweight aluminum alloy according to claim 6, characterized in that: In S2, the amount ratio of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-oxydiphthalic anhydride and 3-aminophenylacetylene is (3.75-7.5) g: (1.25-2.5) g: (15.15-30.3) g: (5.86-11.72) g, the mechanical stirring time is 30-45 min, the reaction time is 5-7 h, the continued reaction time is 2-3 h, the low temperature reaction temperature is -15 to -20 ° C, the reaction time is 10-12 h, the mixture, N,N-dimethyl The dosage ratio of methyl methamide and xylene is (45-50) mL: (45-55) mL: (25-33) mL, the dehydration time is 8-10 h, and the mixture is washed with ethanol 3-5 times. The vacuum drying temperature is 140-160° C. and the time is 2-3 h. In S3, the dosage ratio of component 1 to component 2 is (20-23) g: (10-12) g, the magnetic stirring time is 30-45 min, and a vacuum degassing apparatus is used for degassing, the vacuum degree is 1 kPa, the rotation speed is 2000 rpm, and the running time is 3 min.

9. A method for preparing a high-strength and lightweight aluminum alloy as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Step (1): adding the composite alloy material into a smelting furnace and heating it until it is melted, introducing nitrogen during the smelting process, then adding the prepared composite organic refiner into the smelting furnace, stirring, and then pouring the smelted and refined composite alloy material into a mold, and after cooling and solidification, taking out the aluminum alloy casting; Step (2): grinding and polishing the aluminum alloy casting, then coating the surface with an organic coating, heating it, cutting, drilling and cleaning it to obtain a high-strength and lightweight aluminum alloy.

Citation Information

Patent Citations

  • A high-strength aluminum alloy and its applications

    CN114369745B

  • Pressure-resistant soluble cast aluminum matrix composite material and preparation method thereof

    CN107151754A

  • Aluminum alloy material for mechanical products

    CN107604214A

  • Preparation technology of corrosion-resistant aluminum alloy material and corrosion-resistant aluminum alloy material

    CN107739857A

  • Aluminum alloy material used for mechanical and electrical products

    CN107739903A